A ginsenoside metabolite and its derivative target PRELID3B against lung cancer cells - Jilin He; Chun-Nam Lok; Guanya Yang; Ying He; Yungen Liu; Amir Ata Saei; Yiwei Zhang; Chunlei Zhang; Yanting Zhu; Zhiwen Fu; Christian Michel Beusch; Pierre Sabatier; et al. (Proceedings of the National Academy of Sciences, 2026)
Ginseng is widely praised for its benefits on cancer patients, often attributed to its metabolite compound K ( CK ). Here, we synthesized a derivative ( CKD-4 ) that, compared with CK , exhibited enhanced cellular uptake, threefold greater cytotoxicity, and improved pharmacokinetics. CKD-4 induced significant growth inhibition on lung cancer patient-derived organoids, and on cell line-derived xenografts with minimal systemic toxicity. CKD-4 also suppressed orthotopic lung tumor growth in immunocompetent mice with enhanced antitumor immune infiltration. Using proteome integral solubility alteration and ProTargetMiner analyses, the mitochondrial phospholipid transfer protein PRELID3B was unbiasedly identified as a shared anticancer target of CK and CKD-4 . PRELID3B is a potential pancancer therapeutic target and prognostic biomarker supported by cancer genetics and transcriptomics evidence. Both CK and CKD-4 stabilize PRELID3B in cellular thermal shift assay and bind PRELID3B with K d of 23 µM and 5 µM, respectively, measured by biolayer interferometry. Multiomics analyses revealed that CK and CKD-4 share similar anticancer mechanisms, involving mitochondrial phospholipid depletion, integrated stress response activation, and immunomodulatory pathways induction associated with PRELID3B inhibition. This study provides the basis for the immunomodulatory and anticancer effects of ginseng metabolites through targeting PRELID3B, and illustrates the application of orthogonal proteomics in target identification of natural compounds.